Upaya Guru Pendidikan Agama Islam dalam Membentuk Disiplin Belajar Siswa melalui Pemberian Reward di Kelas 1 SDIT Asy Syaamil Bontang Selatan - Mita, Dela; Husain, Ahmadi (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This article discusses the efforts of Islamic Religious Education Teachers in forming student learning discipline. Learning discipline is one of the important factors that determine students’ academic success. Islamic Religious Education teachers have efforts not only in delivering religious material, but also in forming students’ character and discipline from an early age. One effort that can be applied is through giving rewards. This study aims to (1) determine the efforts of Islamic Religious Education teachers in forming student learning discipline through giving rewards (2) and how the application of these rewards can form student learning discipline. The research used is qualitative with a descriptive approach. Data collection techniques are carried out through observation, interviews, self-assessment and documentation. The subjects of the study were Islamic Religious Education teachers and class 1B students. Data analysis used is Data Reduction, Data Presentation, and Conclusion Drawing. The results of the study show that Islamic Religious Education teachers play an active role in forming student discipline through various strategies, such as role models, direction, positive reinforcement, and the application of rewards given in the form of verbal praise, star stickers, and stationery. Rewards are given fairly, consistently, and educationally, so as to foster student motivation to attend on time, complete assignments, and behave orderly during learning. In addition, the implementation of rewards also creates a positive, active, and enjoyable learning atmosphere. The conclusion of the research results is that the efforts of Islamic Religious Education teachers supported by the implementation of rewards are effectively able to form and strengthen students’ learning discipline from an early age.